Literatur und Emanzipation von Frauen in der Frühromantik : Bettine von Arnim und Karoline von Günderrode - Klipp, Veronica (German Language and Literature, 2016)
Early German Romanticism is a period associated in literary analysis with the emancipation of women. Two women writers of the time. Bettine von Arnim and Karoline von Günderrode take up the Romantic view of literature as an emancipating medium. The thesis refers to Romanticism to define the concepts of feminity, literature and emancipation within their historical context. Romanticism attempts a dialogue between the self and its other, and ultimately re-defines woman as the other of the author male. Friedrich Schlegel's novel Lucinde is analysed as a paradigmatic example of the identification of the self through the medium of literature. The writings of Bettine and Karoline have been analysed as early examples of a feminist literary tradition from the standpoint of feminist theory located in the context of modern women's movements. By way of contrast to Romantic literary theory, this feminist literary theory is expressed as a perceived continuity of women's experience. The concept of self-realisation of women authors through literature is examined from the standpoint of understanding literary texts as objectification of self. French feminist criticism is employed to analyse the relation of feminity to systems of representations from the perspective of modern textual practice. It is argued that Bettine's novel is structured around the literary correspondence between herself and Karoline in which they were able to create a "free-space" (Freiraum) in order to discuss their alienation from society. In realising Romanticism's concept of a dialogue. Bettine achieves a new concept of authorship which allows a representation of female desire, as defined by French theory, through a reflection in Karoline as her other. While both women enjoy the advantage of education. Bettine rejects this as an example of male norms. Karoline imitates these norms to emancipate herself. Karoline identifies with the dominant aesthetic norms in her poetry in an attempt at identification. Her letters, on the other hand, reflect a modern experience of discontinuity of self, which she explains as a result of the absence of social practice in the society of her time and the limitations imposed on her as a woman. In the thesis, it is concluded that Karoline's production is difficult to reconcile with either of the above literary theories. Neither Karoline's nor Bettine's literature can be seen as representative of a unified female subject. The medium of literature enables the development of an aesthetic subjectivity, which, it is argued, can be applied to women-specific" (frauenspezifisch) criticism.